Shift in Icelandic Plant Populations Due to Climate Change: Through the Lens of Natural Dyes - Pluenneke, Molly (SIT Digital Collections, 2017)
Northern residing plant species are at the highest risk for extinction due to temperature rise related to climate change (Schöb, Manuel, Choler & Veit, 2009). Climate change has also led to a northern shift in the geographic distribution of plant species (Parmesan & Yohe, 2003). This could lead to a necessary alteration in the way natural resources are utilized in arctic countries like Iceland (Lim-Camacho et al, 2017). The purpose of this study is to analyze the way in which Icelandic plant species used in natural dye practices may shift in distribution due to climate change and the potential impact this shift may have on the craft. In this study, six plant species used for natural textile dyeing in Iceland were processed into dyes and applied to Icelandic wool. The dyed wool was then woven into an art piece representative of the findings of this study. Through analysis of previous literature on tundra species used in dyeing, the study concludes that a decrease in species diversity and an increase of invasive plant species will occur due to increased temperatures. An increase of new species could lead to new opportunities in the color palette but the increase of invasive species could lead to extinction of commonly used native species that produce unique colors. While some native species like Rumex longifolius will benefit from climate change, other native species will falter. This means that natural dye practitioners in Iceland will begin to see a decrease in the availability of commonly used native species like Cladonia chlorophaea, Peltigera canina and Alchemilla vulgaris and will have to be more mindful when gathering and using them.